Calculation of Primary and Secondary Carbon Footprint in the Environment of Sahid University Jakarta - Sukamdani, Hariyadi B; Sukwika, Tatan (The Graduate School of Sahid University, 2025)
This study aims to identify and measure the primary and secondary carbon footprints within the environment of Sahid University Jakarta. As an educational institution, a university plays a strategic role in climate change mitigation; however, most campuses in Indonesia have not yet optimally implemented environmentally friendly practices. Sahid University Jakarta is among the institutions that have not been classified as a green campus in the UI GreenMetric rankings. This study was conducted in the Faculty of Engineering using a descriptive-analytical quantitative approach, combining primary data (surveys and observations) and secondary data (campus reports). Carbon footprint calculations were based on emission standards from the IPCC and EPA. The results show that the total annual carbon emissions from campus activities reached 542.14 tons of CO₂-eq, with the largest contributions coming from the use of air conditioning (49.29%) and desktop computers (24.16%). Primary carbon emissions dominate the total footprint compared to secondary emissions, such as those from the use of LPG and paper. These findings highlight the need for mitigation strategies focused on managing electricity consumption, particularly for cooling systems and electronic devices.